Movement characteristics, physiological and perceptual responses of elite standard youth football players to different high intensity running drills - Gibson, N. V.; Henning, G.; Twist, C. (Science and Medicine in Football, 2018)
Purpose: To examine responses to high intensity running drills in youth football players. Methods: Seventeen players completed the YoYo Intermittent Recovery test level one (YYIR1) and a 15 m maximal sprint to quantify target running speeds. Players performed three conditions on separate occasions comprising: 12 × 15 s high intensity runs at 100% of the final YYIRT1 speed, 12 × ~ 4 s repeated sprints with ~26 s recovery, and combination running using both modalities. Heart rate was monitored continuously with PlayerLoadTM and movement characteristics using microtechnology. Ratings of perceived exertion and blood lactate responses were measured 2 min after the final repetition. The ratio of Flight:contraction time was calculated from a countermovement jump before and at 2 min and 14 h after each condition. Data analysis used magnitude based inferences and effect sizes statistics. Results: Peak speed (1.1%; ES 0.23 ± 0.44) and mean speed over the initial 4 s (6.3%; ES 0.45 ± 0.46) were possibly faster during combination compared to high intensity running with unclear differences compared to repeated sprinting. This was despite most likely (21.6%; ES 7.65 ± 1.02) differences in prescribed speeds between conditions. There were likely reductions in F:C at 14 h ratio after high intensity (-5.6%; ES - 0.44 ± 0.32) and combination running (-6.8%; ES -0.53 ± 0.47). Changes in the repeated sprinting condition were unclear. Conclusions: Actual movement characteristics of high intensity running drills may not reflect those used to prescribe them whilst reductions in F:C ratio are evident 14 h after their completion.